Beyond Patrimonial Plunder: The Use and Abuse of Coconut Levies in the Philippines. Issue 4 (4th July 2019) - Ramos, Charmaine G.
ABSTRACT: This article re-examines a case of corruption that was perpetuated during a period of authoritarian rule in the Philippines: the subversion of 'coconut levies', a tax on coconut production imposed by strongman President Ferdinand Marcos from 1971 to 1982. Literature on the case has formed the basis for locating the political origins of the country's struggles with long-run economic transformation in terms of the extent of 'rent-seeking' and articulations of 'neo-patrimonialism' in this middle-income developing economy. The article interrogates how extant analyses of the case have explained associated malign developmental outcomes with reference to institutional design and governance conditions. It forwards a re-interpretation that focuses on the distributional contest underpinning levy mobilisation, including the types of state-engineered privileges contested, and how access to these were politically determined and regulated during and after the Marcos period. This approach, in which developmental possibilities of rent-creating state interventions are not universally denied but considered with reference to configurations of power and structures of political bargaining, will be shown to address limitations of preponderant analyses and bear relevance to developing countries where, because of structural reasons, neo-patrimonialism may be endemic but rent-creating state interventions cannot be discounted as instruments for promoting economic development.